Replacing soya bean meal with heat-treated, low-glucosinolate rapeseed meal does not affect the perfomance of growing-finishing pigs did not affect the performance of growing and finishing pigs - Siljander-Rasi, Hilkka; Valaja, Jarmo; Alaviuhkola, Timo; Rantamäki, Pirjo; Tupasela, Tuomo (nl, 1996)
A growth experiment was conducted to determine the suitability of heat-moisture-treated rapeseed meal (RSM) with a very low glucosinolate (GL) content (2.9 micromol/g defatted meal) as a substitute for soya bean meal (SBM) in pig feeding. The RSM was solvent extracted, toasted at 100 C (45 min.) and heat-moisture treated at 130 C (a few seconds, full-steam stage). In the four barley-based diets, 0, 33, 66 and 100 % of SBM was replaced RSM (Brassica campestris cv. Kulta). The RSM diets were fortified with synthetic lysine to achieve a content of 7.5 g/feed unit (FU) of digestible lysine in the grower and 5.9 g/FU in the finisher diets (1 FU=9.33 MJ NE). A total of 160 pigs (25-100 kg) was used in the trial and each diet was tested with ten pens of four animals (two gilts and two castrated male pigs). The pigs were fed according to Finnish feeding standards, with the daily FU intake restricted to 85-90 % of the ad libitum level. The daily weight gain (WG) in the growing (786, 780, 793 and 784 g/d) and finishing periods (847, 855, 842 and 844 g/d) and the feed energy conversion ratio (19.3, 19.5, 19.3 and 19.8 NE MJ kg/WG in the growing and 28.9, 28.3, 29.0 and 29.4 NE MJ kg/WG in the finishing period) were unaffected by dietary RSM substitution. The slaughter loss percentage of the pigs increased lineary (p<0.05) when SBM was replaced by RSM, but othewise carcass quality was similar. Inclusion of RSM in the diet did not affect the weight ofÿ the thyroid gland of the pigs (6.66, 8.06, 7.17 and 7.00 g). The organoleptic quality of the meat (taste, tenderness and juiciness) was similar in all treatment groups. The intramuscular fat content of the loin, however, declined (p<0.05) with increasing RSM substitution. Our results show that negative effects of GLs may be avoided when intake is below 1.2 mmol/d. Thus heat-moisture-treated RSM with a very low GL content can, when fortified with lysine, be a satisfactory alternative to SBM in restricted feeding, even in the diets of growing (25-50 kg) pigs.
Keywords: Ko; lihasika; sika; rypsirouhe; kasvu; rehut; ruokinta; muuntosuhde; sianliha; pig; growing; rapeseed meal; soya bean meal; glucosinolate; lysine